Forebrain and hindbrain development in zebrafish is sensitive to ethanol exposure involving agrin, Fgf, and sonic hedgehog function. Issue 1 (27th November 2012) - Zhang, Chengjin; Ojiaku, Princess; Cole, Gregory J.
Abstract BACKGROUND: Ethanol is a teratogen that affects numerous developmental processes in the nervous system, which includes development and survival of GABAergic and glutamatergic neurons. Possible molecular mechanisms accounting for ethanol's effects on nervous system development include perturbed fibroblast growth factor (Fgf) and Sonic hedgehog (Shh) signaling. In zebrafish, forebrain GABAergic neuron development is dependent on Fgf19 and Shh signaling. The present study was conducted to test the hypothesis that ethanol affects GABAergic and glutamatergic neuron development by disrupting Fgf, Shh, and agrin function. METHODS: Zebrafish embryos were exposed to varying concentrations of ethanol during a range of developmental stages, in the absence or presence of morpholino oligonucleotides (MOs) that disrupt agrin or Shh function. In situ hybridization was used to analyze glutamic acid decarboxylase (GAD1) gene expression, as well as markers of glutamatergic neurons. RESULTS: Acute ethanol exposure results in marked reduction in GAD1 gene expression in forebrain and hindbrain, and reduction of glutamatergic neuronal markers in hindbrain. Subthreshold ethanol exposure, combined with agrin or Shh MO treatment, produces a similar diminution in expression of markers for GABAergic and glutamatergic neurons. Consistent with the ethanol effects on Fgf and Shh pathways, Fgf19, Fgf8, or Shh mRNA overexpression rescues ethanol‐induced decreases in GAD1 and Atonal1a gene expression. CONCLUSIONS: These studies demonstrate that GABAergic and glutamatergic neuron development in zebrafish forebrain or cerebellum is sensitive to ethanol exposure, and provides additional evidence that a signaling pathway involving agrin, Fgfs and Shh may be a critical target of ethanol exposure during zebrafish embryogenesis. Birth Defects Research (Part A), 2013. © 2012 Wiley Periodicals, Inc.